Case report: Ultrasound-guided bilateral serratus anterior plane block in intensive care unit—An alternative to opioid-sparing postoperative analgesia after sternotomy in infants - Xu, MingZhe; Li, Zhi; He, Yi; Deng, LiJing (Frontiers in Anesthesiology, 2023)
Introduction： The high-opioid technique was applied in the setting of congenital cardiac surgery on the belief of severe pain management and analgesic limitation in children along with delayed extubation time and other side effects. Thoracic nerve blockade demonstrated superior postoperative analgesia and stable haemodynamics and lower perioperative opioid consumption and related complications in cardiac surgery. SAPB is a fascial plane block technique that is considered as an alternative to paravertebral block for perioperative thoracic pain relief, targeting intercostal never. Cases presentation: We present 3 cases to describe the efficacy of SAPB as an alternative to opioid-sparing analgesia performed in infant patients after sternotomy in pediatric cardiac intensive care units. It was used as a part of the perioperative pain management successfully. All patients extubation early and recovery soon with no other complications. Conclusion： SAPB lower perioperative opioid consumption and related complications in cardiac surgery with satisfied postoperative analgesia and stable haemodynamics.